Heat release type sponge capable of being used for effectively adsorbing crude oil in low-temperature environment as well as preparation method and application of heat release type sponge
By preparing heat-release sponges and combining superhydrophobic and magnetic phase-changing core materials, the problems of cumbersome preparation, high cost and high energy consumption in the adsorption and recovery of high-viscosity crude oil on the sea surface are solved, and the low-energy and efficient oil spill treatment effect is achieved.
Patent Information
- Application Number
- CN202411799717.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has problems such as cumbersome preparation, high cost, difficulty in large-scale production and high energy consumption in the field of high-viscosity crude oil adsorption and recovery of sea surface, resulting in low efficiency in handling marine oil spill accidents.
Using the preparation method of heat-release sponge, the sponge is soaked and cured in a mixture of ink-containing diluent and hydrophobic organic polymer materials to form a superhydrophobic ink-modified sponge, and the magnetic phase change core material is fixed inside the sponge to form a "sandwich" structured light/magnetic thermal energy storage composite sponge.
It realizes low energy consumption and efficient adsorption of high viscosity crude oil, simplifies the preparation process, reduces costs, and supports large-scale production, which is suitable for oil spill treatment in low-temperature environments.
Smart Images

Figure CN119524817A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil-water separation application, and more specifically relates to a heat-releasing sponge that can be used to effectively absorb crude oil in a low-temperature environment, and a preparation method and application thereof. Background Art
[0002] Oil spill accidents at sea are one of the most typical and serious environmental pollution accidents in the process of marine resource development. They not only cause serious damage to marine biological resources and the ecological environment, but also bring huge economic losses. The oil floating on the water surface caused by crude oil leakage has the characteristics of large area, thin oil layer and high viscosity. How to deal with oil spill accidents efficiently and at low cost remains a continuous challenge.
[0003] At present, the commonly used methods for oil spill treatment mainly include: (1) in-situ combustion; (2) adsorption; (3) spraying oil spill dispersants; (4) microbial remediation. Among them, the adsorption method is widely regarded as the most environmentally friendly and efficient method for treating marine oil pollution. In order to improve the adsorption performance of adsorbent materials for high-viscosity crude oil, the temperature-sensitive properties of crude oil are utilized to introduce materials with photo / electric / magnetothermal conversion on the surface of the adsorbent material, which can achieve efficient and rapid adsorption of crude oil under different environments. Although great progress has been made in the development of high-performance oil absorbent materials to date, the high energy consumption problem in the crude oil recovery process is still a huge challenge faced in large-scale treatment of marine oil spills.
[0004] Phase change material is a thermal management material that regulates the temperature of the system by absorbing and releasing heat during the phase change process. It can effectively solve the problem caused by the mismatch between the supply and demand of thermal energy in time, space or intensity, thereby maximizing the efficiency of energy utilization. Therefore, coupling phase change materials to adsorption materials is expected to achieve low energy consumption, high efficiency, and continuous adsorption of high-viscosity crude oil for a period of time. The most commonly used method for packaging phase change materials is vacuum impregnation, but this method has the disadvantages of complex process, difficulty in ensuring packaging uniformity, and poor packaging stability, which to a certain extent limits the application of phase change materials in the field of environmental remediation.
[0005] In summary, the following technical difficulties exist in the field of adsorption and recovery of high-viscosity crude oil on the sea surface: cumbersome preparation, high cost, difficulty in large-scale production, high energy consumption during use, etc. Therefore, it is urgent to develop a new type of oil-absorbing material with simple preparation process, low cost and low energy consumption, so as to achieve efficient and rapid treatment of marine oil spill accidents. Summary of the invention
[0006] The purpose of the present invention is to provide a heat-releasing sponge that can be used to effectively absorb crude oil in a low-temperature environment, and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art, realize the preparation of a new type of oil-absorbing material with simple preparation process, low cost and low energy consumption, and lay a good foundation for efficiently and quickly handling marine oil spill accidents.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing a heat-releasing sponge that can be used to effectively absorb crude oil in a low-temperature environment, comprising the following steps:
[0009] The sponge is sequentially immersed in a diluent containing ink and a mixed solution containing a hydrophobic organic polymer material, and then solidified to obtain a super-hydrophobic ink-modified sponge;
[0010] The magnetic metal wire is fixed inside the hose, and the phase change material is injected into the hose, and the hose is sealed to obtain the magnetic phase change core material;
[0011] The magnetic phase-change core material is fixed inside the super-hydrophobic ink modified sponge to obtain the heat-releasing sponge.
[0012] The present invention first performs ink modification and super-hydrophobic treatment on the sponge. The ink modification and super-hydrophobic treatment can significantly improve the following properties of the sponge: (1) imparting photothermal conversion performance: the carbon nanoparticles in the ink form a uniform coating with wide-spectrum light absorption ability on the surface of the sponge, so that the sponge exhibits good photothermal conversion performance; (2) hydrophobic modification: the sponge can absorb the carbon particles in the ink and provide a rough surface, and then a super-hydrophobic oil-absorbing sponge can be obtained through hydrophobic treatment. The ink modification and super-hydrophobic treatment can significantly improve the sponge's absorption capacity for a variety of oils and organic solvents.
[0013] The present invention then places the magnetic phase change core material prepared by the filling method into the sponge; the filling method effectively solves the complex problems of vacuum impregnation method encapsulation of phase change materials, such as complex process, difficult to ensure encapsulation uniformity, poor encapsulation stability, etc., effectively avoids the dissolution of molten phase change materials, and ensures high encapsulation stability and uniformity; the introduction of magnetic metal wires into the phase change core material can play a role in magnetothermal conversion and heat conduction; in addition, the sponge modified by ink and super-hydrophobic modification and the magnetic phase change core material can cooperate to make the adsorption material have both light / magnetothermal effect and energy storage performance; Specifically, (1) the carbon nanoparticles in the ink have excellent photothermal properties and can heat up quickly under light, significantly reducing the viscosity of crude oil, thereby enhancing the sponge's adsorption capacity for high-viscosity oil spills. The synergistic phase change core material can ensure that the composite sponge has excellent photothermal conversion and energy storage performance; (2) the iron wire fixed inside the silicone tube is a ferromagnetic material. In the alternating magnetic field, the iron wire will generate eddy currents due to electromagnetic induction, which will then be converted into heat through the resistance of iron, causing the material temperature to rise. Further synergistic phase change materials can make the composite sponge have magnetothermal conversion and energy storage performance. The phase change material can effectively store the heat generated by the iron wire and release it when the energy input is insufficient, thereby ensuring that the composite sponge can maintain a high temperature level for a long time.
[0014] The heat-releasing sponge obtained by the invention can continuously promote crude oil adsorption, thereby realizing low energy consumption and high-efficiency recovery of high-viscosity crude oil.
[0015] Optionally, the sponge includes one or both of melamine sponge and polyurethane sponge; the ink includes one or both of carbon ink and graphene ink; the magnetic metal wire includes one or both of iron wire and nickel-iron alloy wire; the hose includes one or both of silicone tube and thermoplastic elastomer tube; the phase change material includes one or both of polyethylene glycol and solid paraffin.
[0016] Preferably, the molecular weight of the polyethylene glycol is 4000-10000.
[0017] Optionally, the solvent in the diluent containing ink includes one or more of ethanol, isopropanol and n-butanol.
[0018] Preferably, the volume ratio of the ink to the solvent in the ink-containing diluent is 1-3:10-30.
[0019] Optionally, the hydrophobic organic polymer material includes polydimethylsiloxane and / or polyvinylidene fluoride; and the solvent of the mixed solution containing the hydrophobic organic polymer material includes one or more of isopropanol, cyclohexane and ethyl acetate.
[0020] Preferably, the concentration of the hydrophobic organic polymer material in the mixed solution containing the hydrophobic organic polymer material is 10 to 30 mg / mL.
[0021] Preferably, the immersion time is 1 to 3 minutes; the curing temperature is 70 to 90° C., and the curing time is 3 to 6 hours.
[0022] Preferably, after the sponge is immersed in the diluent containing the ink, a subsequent drying step is also included.
[0023] Furthermore, the ink-containing diluent is prepared from ink and ethanol; the volume fraction of the ink is 10-50%; the soaking time is 3-6 minutes; the drying temperature is 40-80° C., and the drying time is 3-6 hours.
[0024] Preferably, the relationship between the length of the sponge, the length of the hose and the length of the magnetic metal wire is: the length of the sponge ≥ the length of the hose > the length of the magnetic metal wire; the inner diameter of the hose is 0.5-4.75 mm, and the outer diameter of the hose is 1-5 mm; the diameter of the magnetic metal wire is 0.3-0.95 mm; the inner diameter of the hose > the diameter of the magnetic metal wire.
[0025] Furthermore, on the basis of satisfying the above conditions, the dimensions of the sponge, hose and magnetic wire are further preferably 4-10cm×3-8cm×0.5-2.5cm, more preferably 6cm×4cm×1cm, the length of the hose is further preferably 4-10cm, more preferably 6cm, and the length of the wire is further preferably 3-8cm, more preferably 4cm.
[0026] Preferably, the injection amount of the phase change material is 60-90% of the volume of the hose.
[0027] Preferably, the material used for the end-capping includes cotton fiber or kapok fiber.
[0028] The second technical solution of the present invention is to provide a heat-releasing sponge prepared by a method for preparing the heat-releasing sponge that can be used to effectively adsorb crude oil in a low-temperature environment.
[0029] The heat-releasing sponge described in the present invention is a super-hydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge.
[0030] The third technical solution of the present invention is to provide the application of the heat-releasing sponge in oil spill treatment.
[0031] The heat-releasing sponge obtained by the invention can realize low-energy consumption and high-efficiency oil spill treatment.
[0032] The present invention discloses the following technical effects:
[0033] 1. The super-hydrophobic "sandwich" structured light / magnetothermal energy storage composite sponge of the present invention is firstly prepared by impregnating the sponge with ink and further modifying the surface to be hydrophobic, thereby obtaining an outer super-hydrophobic oil-absorbing sponge; then, a simple filling method is used to encapsulate the molten phase change material into a hose fixed with a magnetic metal wire, thereby obtaining a magnetic phase change core material; finally, the outer super-hydrophobic oil-absorbing sponge and the magnetic phase change core material are assembled into a "sandwich" structured light / magnetothermal energy storage composite sponge, and the coupled phase change material can reduce the energy consumption in the crude oil adsorption process to a certain extent by slowly releasing the stored heat;
[0034] 2. The phase change core material of the super-hydrophobic "sandwich" structure optical / magnetothermal energy storage composite sponge of the present invention is prepared by a simple filling method, which can effectively avoid the dissolution of the molten phase change material and ensure high packaging stability and uniformity;
[0035] 3. The super-hydrophobic "sandwich" structure optical / magnetothermal energy storage composite sponge of the present invention has both optical / magnetothermal conversion performance and energy storage-heat release performance. It can not only quickly increase the temperature under light / magnetic field and reduce the viscosity of the oil, but also release the stored heat through the phase change material for a period of time without energy input to keep the composite sponge at a higher temperature level, continuously promote crude oil adsorption, and achieve low energy consumption and efficient recovery of high-viscosity crude oil;
[0036] 4. The raw materials of the super-hydrophobic "sandwich" structure optical / magnetothermal energy storage composite sponge of the present invention are easily available, the preparation process is simple, the cost is low, and it can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The physical picture (a) of the super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge prepared in Example 1 and the physical picture (b) of the phase change core material;
[0038] Figure 2 The SEM images of the super-hydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge prepared in Example 1 at different magnifications;
[0039] Figure 3 The photothermal conversion and energy storage performance test curve of the super-hydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge prepared in Example 1;
[0040] Figure 4 The magnetothermal conversion and energy storage performance test curve of the super-hydrophobic "sandwich" structured light / magnetothermal energy storage composite sponge prepared in Example 1;
[0041] Figure 5 This is the light-to-heat conversion curve of the super-hydrophobic "sandwich" structure composite sponge prepared in Comparative Example 1;
[0042] Figure 6The water contact angle diagrams of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge (b) prepared in Example 1 and the "sandwich" structured light / magnetic thermal energy storage composite sponge (a) prepared in Comparative Example 2;
[0043] Figure 7 The photothermal conversion curve of the super-hydrophobic "sandwich" structured optical / magnetocaloric composite sponge prepared in Comparative Example 3;
[0044] Figure 8 The magnetothermal conversion curve of the super-hydrophobic "sandwich" structured optical / magnetothermal composite sponge prepared in Comparative Example 3;
[0045] Fig. 9 It is a leakage test diagram of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge prepared in Comparative Example 4, wherein a is a surface condition diagram of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge, and b is a leakage trace diagram of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge on the filter paper;
[0046] Fig.10 This is a diagram showing the adsorption effect of crude oil by the superhydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge in Application Example 1 under lightless (a) and lighted (b) conditions;
[0047] Fig.11 This is a diagram showing the adsorption effect of crude oil by the superhydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge in Application Example 2 under conditions of no magnetic field (a) and with magnetic field (b);
[0048] Fig.12 This is a diagram of the crude oil adsorption effect of the superhydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge during the heat release process in Application Example 3. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] The polydimethylsiloxane (PDMS) used in the following examples, comparative examples and application examples is a two-component product of Dow Corning SYLGARD DC184 of the United States, including polydimethylsiloxane and a curing agent, with a mixing mass ratio of 10:1, which is an existing commercially available product;
[0055] The polyvinylidene fluoride (PVDF) used was purchased from Dow Corning.
[0056] Example 1
[0057] This embodiment provides a super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge:
[0058] (1) Cleaning of melamine sponge: The melamine sponge was cut into (length × width × height) 6 cm × 4 cm × 1 cm, and an opening was made in the width direction at the center of the side formed by the width and height, the length of the opening was less than the width of the melamine sponge, and the depth of the opening ensured that a through hole was formed in the middle of the melamine sponge; the cut melamine sponge was ultrasonically treated in anhydrous ethanol for 30 min, then rinsed with deionized water 3 times, and dried in an oven at 60°C for 6 h;
[0059] (2) Carbon ink modification: carbon ink and anhydrous ethanol are mixed in a volume ratio of 2:15 to obtain a carbon ink diluent; the melamine sponge cleaned in step (1) is added to the carbon ink diluent and soaked for 2 minutes, taken out and placed in a 60° C. oven for drying for 12 hours to obtain an ink-modified melamine sponge;
[0060] (3) Hydrophobic modification: 1 g of purchased polydimethylsiloxane and 0.1 g of curing agent were added to 50 mL of isopropanol, and stirred at room temperature for 30 min to make them evenly dispersed. The ink-modified melamine sponge prepared in step (2) was placed in the above solution for 1 min, taken out and cured in an oven at 80° C. for 5 h to obtain a super-hydrophobic ink-modified melamine sponge;
[0061] (4) Packaging of polyethylene glycol: Take a 6 cm long silicone tube (outer diameter 4 mm, tube wall thickness 0.5 mm), fix a 4 cm long iron wire (diameter 0.95 mm) inside the silicone tube; place polyethylene glycol (molecular weight 6000) in a beaker, and heat it in an 80°C water bath for 30 min to obtain molten polyethylene glycol; use a syringe to inject the molten polyethylene glycol into the silicone tube, and the injection amount is 70% of the volume of the silicone tube; finally, seal both ends with cotton fiber to obtain a magnetic phase change core material;
[0062] (4) Structural assembly: Arrange five magnetic phase change core materials prepared in step (4) in parallel and fix them at the opening positions of the superhydrophobic ink-modified melamine sponge prepared in step (3) to obtain a superhydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge.
[0063] Figure 2 The SEM images of the super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge prepared in Example 1 at different magnifications. Figure 2 It can be seen that the sponge impregnated with carbon ink and further hydrophobically modified still maintains a porous structure.
[0064] Figure 3 The photothermal conversion and energy storage performance test curve of the super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge prepared in Example 1. Figure 3 It can be seen that the composite sponge is 2 The temperature can rise to 76°C under high light intensity. After turning off the light source, the cooling curve shows a temperature platform at around 40°C, indicating that it has good photothermal conversion and energy storage performance.
[0065] Figure 4 The magnetothermal conversion and energy storage performance test curve of the super-hydrophobic "sandwich" structured light / magnetothermal energy storage composite sponge prepared in Example 1. Figure 4 It can be seen that the temperature of the composite sponge can quickly rise to 59°C when placed in an alternating magnetic field with an alternating current of 6A. After turning off the light source, the cooling curve shows a temperature platform at around 40°C, indicating that it has good magnetothermal conversion and energy storage performance.
[0066] Example 2
[0067] This embodiment provides a super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge:
[0068] The difference from Example 1 is that "1 g of polydimethylsiloxane and 0.1 g of curing agent" in Example 1 are replaced with an equal amount of polyvinylidene fluoride, and the rest is the same as Example 1.
[0069] Example 3
[0070] This embodiment provides a super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge:
[0071] The difference from Example 1 is that the "injection amount is 70% of the volume of the silicone tube" in Example 1 is adjusted to "injection amount is 60% of the volume of the silicone tube", and the rest is the same as Example 1.
[0072] Example 4
[0073] This embodiment provides a super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge:
[0074] The difference from Example 1 is that the "injection amount is 70% of the volume of the silicone tube" in Example 1 is adjusted to "injection amount is 80% of the volume of the silicone tube", and the rest is the same as Example 1.
[0075] Comparative Example 1
[0076] This comparative example provides a super-hydrophobic "sandwich" structure composite sponge:
[0077] The difference from Example 1 is that step (2) carbon ink modification is omitted, and the rest is the same as Example 1.
[0078] Figure 5 The photothermal conversion curve of the super hydrophobic "sandwich" structure composite sponge prepared in Comparative Example 1 is shown in FIG. Figure 5 It can be seen that the sponge is at 100mW / cm 2 The temperature only reached 40°C under the light intensity, indicating that it has no photothermal conversion ability.
[0079] Comparative Example 2
[0080] This comparative example provides a "sandwich" structured light / magnetic thermal energy storage composite sponge:
[0081] The difference from Example 1 is that step (3) hydrophobic modification is omitted, and the rest is the same as Example 1.
[0082] Figure 6 The water contact angle diagrams of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge (b) prepared in Example 1 and the "sandwich" structured light / magnetic thermal energy storage composite sponge (a) prepared in Comparative Example 2 are shown in FIG. Figure 6It can be seen that the water droplets of pure water on the surface of the composite sponge obtained in Example 1 are spherical, with a contact angle of 157.7°, showing super hydrophobicity. However, the water contact angle of the composite sponge obtained in Comparative Example 2 is 0°, which does not have hydrophobicity.
[0083] Comparative Example 3
[0084] This comparative example provides a super-hydrophobic "sandwich" structured light / magnetocaloric composite sponge:
[0085] The difference from Example 1 is that the encapsulation of polyethylene glycol in step (4) is replaced by "taking a 6 cm long silicone tube (outer diameter 4 mm, tube wall thickness 0.5 mm), fixing a 4 cm long iron wire (diameter 0.95 mm) inside the silicone tube, and sealing both ends with cotton fiber to obtain a magnetic core material"; the rest is the same as Example 1.
[0086] Figure 7 The photothermal conversion curve of the super-hydrophobic "sandwich" structured optical / magnetocaloric composite sponge prepared in Comparative Example 3; Figure 8 This is the magnetothermal conversion curve of the super-hydrophobic "sandwich" structured optical / magnetothermal composite sponge prepared in comparative example 3. Figure 7 and Figure 8 It can be seen that the composite sponge obtained in Comparative Example 3 only has light / magnetothermal conversion performance, but does not have thermal energy storage function.
[0087] Comparative Example 4
[0088] This comparative example provides a super-hydrophobic "sandwich" structured optical / magnetocaloric composite sponge prepared by a vacuum impregnation method:
[0089] The difference from Comparative Example 3 is that after step (2), a step of impregnating the phase change material is added, specifically, 5 g of polyethylene glycol is dissolved in 12 mL of ethanol, vigorously stirred at 70° C. until completely melted, the ink-modified melamine sponge is added to the melted polyethylene glycol, the polyethylene glycol is uniformly loaded by repeatedly squeezing the ink-modified melamine sponge, and then the sample is taken out and placed in a vacuum oven at 80° C. to dry for 24 hours. Other steps are the same as those of Comparative Example 3.
[0090] The super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge obtained in this comparative example was placed on filter paper, placed at 80°C and observed for leakage. The results are as follows: Fig. 9 shown.
[0091] Fig. 9This is a leakage experiment test diagram of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge prepared in Comparative Example 4, wherein a is a surface condition diagram of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge, and b is a leakage trace diagram of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge on the filter paper; from the leakage traces on the filter paper, it can be seen that the composite sponge prepared by the vacuum impregnation method will leak at high temperature and does not have good shape stability.
[0092] Application Example 1
[0093] The super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge obtained in Example 1 was used to adsorb high-viscosity crude oil under illumination:
[0094] Take a piece of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge obtained in Example 1, and drop a high-viscosity crude oil with a viscosity of 21176.7 mPa·s at room temperature on the surface of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge; first, let it stand for 3 minutes in the dark to observe the penetration of crude oil on the sponge surface, and then apply 100 mW / cm 2 The penetration of high-viscosity crude oil on the surface of the super-hydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge was observed, and the changes in the surface temperature of the sample were recorded with a thermal imager. The results are as follows: Fig.10 shown.
[0095] Fig.10 This is a diagram showing the adsorption effect of crude oil by the superhydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge in Application Example 1 under lightless (a) and lighted (b) conditions. Fig. 9 It can be seen that in the absence of light, after standing for 3 minutes, the oil droplets did not undergo obvious changes. When light was applied, the surface temperature of the sample rose rapidly, and the oil droplets were quickly adsorbed by the sample. After 3 minutes, all the oil droplets were absorbed.
[0096] Application Example 2
[0097] The super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge obtained in Example 1 was used to adsorb high-viscosity crude oil in a magnetic field:
[0098] Take a piece of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge obtained in Example 1, and drop a high-viscosity crude oil with a viscosity of 21176.7 mPa·s at room temperature on the surface of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge; first, let it stand for 3 minutes without an external magnetic field to observe the penetration of the crude oil on the sponge surface, then pass a 6A alternating current to generate an alternating magnetic field, continue to observe the penetration of the high-viscosity crude oil on the surface of the super-hydrophobic "sandwich" structured light / magnetic thermal energy storage composite sponge, and use a thermal imager to record the change in the surface temperature of the sample. The results are as follows: Fig.11 shown.
[0099] Fig.11 This is a diagram showing the adsorption effect of crude oil by the superhydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge in Application Example 2 under conditions of no magnetic field (a) and with magnetic field (b). Fig.10 It can be seen that in the absence of an external magnetic field, the oil droplets did not undergo obvious changes after standing for 3 minutes. When an alternating current was passed, the surface temperature of the sample rose rapidly due to electromagnetic induction heating, and the oil droplets were quickly adsorbed by the sample. After 3 minutes, all the oil droplets were absorbed.
[0100] Application Example 3
[0101] The super-hydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge obtained in Example 1 was used for heat release-assisted adsorption of high-viscosity crude oil:
[0102] The super-hydrophobic "sandwich" structured optical / magnetothermal energy storage composite sponge obtained in Example 1 was placed under 100 mW / cm 2 Under light, use a thermal imager to record the change of sample surface temperature. After the surface temperature rises to a stable state, turn off the light source and quickly drip high-viscosity crude oil with a viscosity of 21176.7 mPa·s at room temperature on the surface to observe the penetration of the oil droplets. After the oil droplets have completely penetrated, drip high-viscosity crude oil with a viscosity of 21176.7 mPa·s at room temperature again. Repeat this process until the surface oil droplets can no longer be adsorbed, and record the number of times the high-viscosity crude oil is dripped. The results are as follows: Fig.12 shown.
[0103] Fig.12 This is a diagram showing the adsorption effect of the superhydrophobic "sandwich" structured optical / magnetic thermal energy storage composite sponge on high-viscosity crude oil during the heat release process in Application Example 3. Fig.12 It can be seen that the surface temperature of the sample slowly decreases after preheating under light, and the crude oil added six times in a row can completely penetrate into the interior of the sample, indicating that the product of the present invention can achieve efficient and continuous adsorption of crude oil by slowly releasing the stored heat through the phase change material within a period of time without energy input.
[0104] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0105] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a heat-releasing sponge that can be used to effectively absorb crude oil in a low-temperature environment, characterized in that: The steps include: The sponge is sequentially immersed in a diluent containing ink and a mixed solution containing a hydrophobic organic polymer material, and then solidified to obtain a super-hydrophobic ink-modified sponge; The magnetic metal wire is fixed inside the hose, and the phase change material is injected into the hose, and the hose is sealed to obtain the magnetic phase change core material; The magnetic phase-change core material is fixed inside the super-hydrophobic ink modified sponge to obtain the heat-releasing sponge.
2. The preparation method according to claim 1, characterized in that: The sponge includes one or both of melamine sponge and polyurethane sponge; and / or the ink includes one or both of carbon ink and graphene ink; and / or the magnetic metal wire includes one or both of iron wire and nickel-iron alloy wire; and / or the hose includes one or both of silicone tube and thermoplastic elastomer tube; and / or the phase change material includes one or both of polyethylene glycol and solid paraffin.
3. The preparation method according to claim 1, characterized in that: The solvent in the diluent containing ink includes one or more of ethanol, isopropanol and n-butanol; and / or the volume ratio of the ink to the solvent in the diluent containing ink is 1-3:10-30.
4. The preparation method according to claim 1, characterized in that: The hydrophobic organic polymer material includes polydimethylsiloxane and / or polyvinylidene fluoride; and / or, the solvent of the mixed solution containing the hydrophobic organic polymer material includes one or more of isopropanol, cyclohexane and ethyl acetate; and / or, the concentration of the hydrophobic organic polymer material in the mixed solution containing the hydrophobic organic polymer material is 10 to 30 mg / mL.
5. The preparation method according to claim 1, characterized in that: The immersion time is 1 to 3 minutes; and / or the curing temperature is 70 to 90° C. and the curing time is 3 to 6 hours.
6. The preparation method according to claim 1, characterized in that: After the sponge is soaked in the diluted liquid containing the ink, a subsequent drying step is also included.
7. The preparation method according to claim 1, characterized in that: The relationship between the length of the sponge, the length of the hose and the length of the magnetic metal wire is: the length of the sponge ≥ the length of the hose > the length of the magnetic metal wire; and / or the inner diameter of the hose is 0.5-4.75 mm, and the outer diameter of the hose is 1-5 mm; and / or the diameter of the magnetic metal wire is 0.3-0.95 mm; and / or the inner diameter of the hose > the diameter of the magnetic metal wire.
8. The preparation method according to claim 1, characterized in that: The injection amount of the phase change material is 60-90% of the volume of the hose.
9. The heat-releasing sponge prepared by the method for preparing the heat-releasing sponge capable of effectively absorbing crude oil in a low-temperature environment according to any one of claims 1 to 8.
10. Use of the heat-releasing sponge according to claim 9 in oil spill treatment.